Development of Educational Media for Adolescent Reproductive Health - Wulandari, Lisa Purbawaning; Apsari, Duhita Dyah; Hapsari, Anindya (Futurity Medicine, 2023)
The starting point for the human life cycle in preparing for a healthy reproductive process begins during adolescence. During adolescence, rapid hormonal, physical, psychological and social changes occur. Preparing teenagers from physical, mental and social aspects is very important. The current lack of knowledge among teenagers can result in problems for teenagers related to reproductive health. Hence, scientific researchers aim to develop a media application model that can effectively disseminate knowledge and information regarding adolescent reproductive health education. Developing this application is a dedicated endeavour to deliver accessible education to teenagers about adolescent reproductive health in an easy and fun way. Aims: This research aimed to develop educational media and analyse the suitability of the media from material experts, media experts and users. Study design: The type of research was the Research and Development (RnD) using the ADDIE research and development model (Analysis, design, Development, Implementation, Evaluation) by Robert Maribe Branch. This research step uses 3 stages, namely needs analysis, design creation and development stages which will be validated by material experts, media experts and users. The research instrument used a questionnaire with a Likert scale and was analysed to see the feasibility classification. Results: This research produced educational media for adolescent reproductive health which has screening, education and educational game features. The results of the material expert assessment were 87.5% (very worth it), media experts 95.2% (very worth it) and 50 teenage respondents (100%) assessed this media as very suitable for use. Conclusion: The development of website-based adolescent reproductive health education media has been carried out and received a very appropriate classification from material experts, media experts and users. This media is very suitable to be applied to teenagers as an effort to increase knowledge about reproductive health in an easy and fun way. Apart from that, this media can be accessed anytime and anywhere by teenagers. The starting point for the human life cycle in preparing for a healthy reproductive process begins during adolescence. During adolescence, rapid hormonal, physical, psychological and social changes occur. Preparing teenagers from physical, mental and social aspects is very important. The current lack of knowledge among teenagers can result in problems for teenagers related to reproductive health. Hence, scientific researchers aim to develop a media application model that can effectively disseminate knowledge and information regarding adolescent reproductive health education. Developing this application is a dedicated endeavour to deliver accessible education to teenagers about adolescent reproductive health in an easy and fun way. Aims: This research aimed to develop educational media and analyse the suitability of the media from material experts, media experts and users. Study design: The type of research was the Research and Development (RnD) using the ADDIE research and development model (Analysis, design, Development, Implementation, Evaluation) by Robert Maribe Branch. This research step uses 3 stages, namely needs analysis, design creation and development stages which will be validated by material experts, media experts and users. The research instrument used a questionnaire with a Likert scale and was analysed to see the feasibility classification. Results: This research produced educational media for adolescent reproductive health which has screening, education and educational game features. The results of the material expert assessment were 87.5% (very worth it), media experts 95.2% (very worth it) and 50 teenage respondents (100%) assessed this media as very suitable for use. Conclusion: The development of website-based adolescent reproductive health education media has been carried out and received a very appropriate classification from material experts, media experts and users. This media is very suitable to be applied to teenagers as an effort to increase knowledge about reproductive health in an easy and fun way. Apart from that, this media can be accessed anytime and anywhere by teenagers.